If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 2x + -3 = 3 Reorder the terms: -3 + m + 2x = 3 Solving -3 + m + 2x = 3 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3' to each side of the equation. -3 + m + 3 + 2x = 3 + 3 Reorder the terms: -3 + 3 + m + 2x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + m + 2x = 3 + 3 m + 2x = 3 + 3 Combine like terms: 3 + 3 = 6 m + 2x = 6 Add '-2x' to each side of the equation. m + 2x + -2x = 6 + -2x Combine like terms: 2x + -2x = 0 m + 0 = 6 + -2x m = 6 + -2x Simplifying m = 6 + -2x
| x+3-(6-15x)=12(6x-4)-3x+4 | | 42+14*3-(26+13)=n | | 7y+2+2y+3=13y-15 | | 43+14*3-(26+13)=n | | 6-7/6 | | 14n-5n^3=0 | | d-1=1/2d-1 | | 8x+4=8+5x | | 8=r-1 | | 50=.7X | | 11x-144000+4x=156000 | | 32-6+9*8=n | | 3600=x+.03x | | 5x^2+15x-140= | | 14-7+5+1=3 | | x/3-13=68 | | 5(x+x)=2x+3 | | k-5/8=1/8 | | 26+28*10=n | | y=-(0)-5 | | 19*11+22=n | | 9/10x-4/10=7/10 | | 4x-1/5=3/5 | | 1/5x-4/5=2/5 | | (x^2)(-2(-3)-1)= | | 3/10m-2/5=1/10 | | x-7/10=2/10 | | 7/8y-3/8=2/8 | | -304=8(4-7x) | | (1/2)x-6.3=0.7 | | 8=n-84 | | (9/8)x-(7/8)=(1/8) |